2006
DOI: 10.1016/j.palaeo.2005.11.022
|View full text |Cite
|
Sign up to set email alerts
|

Fossil record of holococcoliths and selected hetero-holococcolith associations from the Mediterranean (Holocene–late Pleistocene): Evaluation of carbonate diagenesis and palaeoecological–palaeocenographic implications

Abstract: The Holocene-late Pleistocene distribution of holococcoliths, is quantified by light microscopy from cores from the Western Mediterranean, the Aegean Sea and eight eastern Mediterranean cores recovering sapropel S1. The diversity of fossil holococcoliths is much lower than is seen in the plankton, indicating selective preservation. However the holococcolith phases of Syracosphaera pulchra and Helicosphaera carteri are abundantly preserved allowing a comparison of fossil records of heterococcolith and holococco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 43 publications
2
15
0
3
Order By: Relevance
“…Overgrowths were observed by Crudeli et al (2004Crudeli et al ( , 2006, while studying nanofossils (Emiliania huxleyi). Crudeli et al (2004) suggested that fluctuations in the abundance of nannofossil morphotypes in the Eastern Mediterranean do not necessarily reflect environmental conditions in surface waters (temperature, fertility, etc.…”
Section: Deconvolution Procedures and Quantification Of Diagenetic Calmentioning
confidence: 99%
“…Overgrowths were observed by Crudeli et al (2004Crudeli et al ( , 2006, while studying nanofossils (Emiliania huxleyi). Crudeli et al (2004) suggested that fluctuations in the abundance of nannofossil morphotypes in the Eastern Mediterranean do not necessarily reflect environmental conditions in surface waters (temperature, fertility, etc.…”
Section: Deconvolution Procedures and Quantification Of Diagenetic Calmentioning
confidence: 99%
“…Helicosphaera spp. is known to preferentially high productivity waters in the middle photic zone Crudeli et al, 2006). In this study, the genus Helicosphaera is represented mainly by H. carteri, a species with preference in warm waters (Brand, 1994;Baumann et al, 2005) and moderately elevated nutrient levels (Findlay and Giraudeau, 2000;Andruleit and Rogalla, 2002;Ziveri et al, 2004).…”
Section: Holocene Coccolithophore Assemblages: Paleoecological Groupsmentioning
confidence: 79%
“…The high preservation potentiality of this species has already been reported in late Quaternary Mediterranean sediments, where it occurs with percentage values up to 25-30% . However, we note that Crudeli et al (2006) ruled out from their quantitative counts specimens of E. huxleyi, gephyrocapsids and F. profunda. Thus the abundance reported in the present study for S. pulchra HOL oblonga may even be higher than in the eastern Mediterranean cores.…”
Section: Glacials and The Response To Suborbital Climatic Fluctuationsmentioning
confidence: 92%
“…A further strong evidence of decreased productivity during MIS 3 and MIS 2 cold spells is the correlation between Miscellaneous taxa and holococcoliths (S. pulchra HOL oblonga) (Figs 4 and 5), that are typical of warm and oligotrophic water and in fact they are especially abundant in the eastern Mediterranean Sea (e.g., Kleijne, 1991;Knappertsbusch, 1993;Winter et al, 1994;Crudeli et al, 2006;Malinverno et al, 2009). The high preservation potentiality of this species has already been reported in late Quaternary Mediterranean sediments, where it occurs with percentage values up to 25-30% .…”
Section: Glacials and The Response To Suborbital Climatic Fluctuationsmentioning
confidence: 98%